2006
DOI: 10.1016/j.ssi.2006.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion behavior of transition metals in field-assisted ion-exchanged glasses

Abstract: The use of ion-exchange techniques for doping silicate glasses with transition metals has attracted much attention in the last decades for its potential in several applications, namely, light waveguides technology, luminescent materials, and for the possibility to realize systems in which metal nanocluster formation is controlled by suitable post-exchange techniques. In this framework, the control of metal distribution inside the glass is a central issue for both the understanding of the incorporation process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…Much work has been done with this technique in the case of the diffusion of monovalent ions into soda-lime and borosilicate glasses [11][12][13][14][15], where the dopant ions replace alkali ions of the glass matrix. Solid-state field-assisted diffusion has also been realized in more recent years for doping silicate glasses with monovalent [16][17][18] as well as multivalent ions [19,20], but much less attention has been dedicated to the possibility of doping a pure silica matrix, where the penetration of foreign ions should actually depend on defects/impurities as well as local re-arrangements of the structure. In this work, preliminary results are presented for both Ag and Au doping.…”
Section: Introductionmentioning
confidence: 99%
“…Much work has been done with this technique in the case of the diffusion of monovalent ions into soda-lime and borosilicate glasses [11][12][13][14][15], where the dopant ions replace alkali ions of the glass matrix. Solid-state field-assisted diffusion has also been realized in more recent years for doping silicate glasses with monovalent [16][17][18] as well as multivalent ions [19,20], but much less attention has been dedicated to the possibility of doping a pure silica matrix, where the penetration of foreign ions should actually depend on defects/impurities as well as local re-arrangements of the structure. In this work, preliminary results are presented for both Ag and Au doping.…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out in [23], a complete modeling of the ion diffusion process is still lacking. In any case, in the studied samples we showed that by varying the applied electric field, the depth distribution of Ag can be modified, with a concentration maximum at the surface (V EFAD = 0.4 kV), as usual in field assisted film dissolution [24], or at certain depth within the glass (V EFAD = 1.6 kV), that has been previously associated to a lack of local charge neutrality due to structural network modifications upon the formation of a strongly depleted region [14]. Such region can be formed as the applied electric field is higher.…”
Section: Discussionmentioning
confidence: 71%
“…In this way the oxide layer at the interface can supply Ag + for ion diffusion upon application of electric field [22]. In addition alkali ion migration of native ions inside the glass (basically Na + ) is faster than the diffusion of metal, generating a space-charge distribution inside the glass and modifying the diffusion of metal ions [14]. Thus, the distribution of metal ions inside the glass depends then in a complex way on the physical and chemical phenomena that take place at the metal-glass interface and in the glass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, several spectroscopic investigations have been performed on the structural rearrangements in silicate glasses doped with silver by different non-equilibrium techniques [30][31][32][33] looking on one hand at a deeper understanding of the silver behavior in the matrix, and on the other hand at a comprehensive phenomenological descripition able to provide suitable recipes for the fabrication of glasses with prescribed features. The diffusion behavior of silver in glasses has been also di object of several dedicated studies: the classical phenomenology of the Nernst-Planck equations, as first described for this case by Doremus [34], has been tested for several Ag-glass systems, demonstrating the need to include local effects of both compositional (pseudo mixed-alkali effect) and electrical (local fields build-up) nature [35][36][37][38], In this perspective, the electrical conductivity properties of silverdoped glasses has been also extensively studied [39][40][41][42] for application purposes.…”
Section: Properties Of Silver-doped Glassesmentioning
confidence: 99%